Euphemism Forms in the Deddy Corbuzier’s Youtube Account Comment Column - Diah Fitriani; Laili Etika Rahmawati (BAHASTRA, 2021)
This study aims to describe the form of euphemism in the comments column of Deddy Corbuzier's Youtube account. This type of research is descriptive qualitative. The data collection technique in this study was the listening technique and the note-taking technique. This study uses a content analysis approach. The data from this study are expressions in the form of words, sentences, and phrases that contain euphemisms contained in the comments column of Deddy Corbuzier's Youtube account. Speech analysis technique in this study uses the equivalent method. This study found 25 data in the form of euphemistic expressions contained in the comments column of Deddy Corbuzier's Youtube account. From the 25 data, there are 10 forms of euphemisms, namely: (1) metaphorical euphemisms where words are ignored and like knights, (2) figurative forms of expression euphemisms include the word natural selection and carrying out a mandate, (3) circumlocutionary euphemisms include the word children of the nation, formality. , and extraordinary, (4) euphemisms in the form of idiomatic phrases include humble words, brilliant thoughts, rare, and right-handed, (5) euphemisms in hyperbole form include words bitter, salty and enlightening thoughts, (6) euphemisms in the form of leasing have formula words ( special) and (angel) protectors, (7) euphemisms in the form of foreign terms include the words low profile, legowo and smart people, (8) euphemisms in the form of one word replacing another word with the word wow, building generations, and begging, (9) euphemisms of the form uptake contains the words salute and appreciation, and (10) euphemisms in the abbreviated form include the words UKT and PJJ.